Flipbook Learning Module for Pancasila Education on Local Batik Culture: Modul Pembelajaran Flipbook untuk Pendidikan Pancasila tentang Budaya Batik Lokal - Azri, Faradisa Hayu Karisma; Tirtoni, Feri (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Indonesian education emphasizes character formation and cultural understanding, especially through the Merdeka Curriculum. Specific Background: Local wisdom such as batik holds philosophical and cultural values that are essential for strengthening the Pancasila Student Profile. Gap: However, learning resources that integrate local cultural content with digital interactive media remain limited. Aim: This article presents the development of a flipbook learning module for Pancasila Education focusing on batik as local wisdom in Sidoarjo. Results: The module contains structured materials, instructional videos, design practice activities, project-based applications, and online quizzes, enabling students to engage actively through a technology-based format. The flipbook provides navigation tools and multimedia elements that support independent and enjoyable learning. Novelty: This module uniquely integrates batik culture with a digital interactive format specifically adapted to elementary learning needs. Implications: The flipbook serves as a practical digital resource for teachers and supports students in appreciating and preserving local wisdom while strengthening character values. Highlights:• Students learn batik through interactive digital modules• Module integrates Pancasila values and local wisdom• Supports active, multimedia-based learning activities Keywords: Flipbook, Batik, Pancasila Education, Digital Module, Local Wisdom